Abe Lincoln log cabin to White House - North, Sterling 1906- (Landmark books, 1956)
A biography of Abraham Lincoln, focusing on his childhood spent in poverty on the Midwestern frontier, and chronicling his rise to the Presidency and the highlights of his tenure.